Young Voices from the Rural Midwest - Joseph J. D'Amico; William Matthes; Anita Sankar; Betty Merchant; Martha Zurita (Journal of Research in Rural Education, 1996)
To find out how youngsters growing up in rural communities across the Midwest see themselves, their families, friends, communities, andfutures, a team ofresearchersfrom the Rural Young Voices Project spoke with teenagersfrom three ofthese rural places. What they found was that despite an ambivalence about their rural experiences and a desire to move elsewhere, these "young voices" make the best of, value, and take joy from living in rural places.